Persistent Increases in Nighttime Heat Stress From Urban Expansion Despite Heat Island Mitigation. Issue 4 (17th February 2021) - Huang, Kangning; Lee, Xuhui; Stone, Brian; Knievel, Jason; Bell, Michelle L.; Seto, Karen C.
Abstract: Urban areas generally have higher near‐surface air temperature and lower air humidity than rural areas. Little is known about how heat stress, the combined effect of high air temperature and high humidity on human physiology, will be affected by future urban land expansion. Here we use a mesoscale numerical weather prediction model to examine the effects of urban land expansion from 2000 to 2050 on heat stress (measured as wet‐bulb globe temperature, WBGT) in the urban areas of China, India, and Nigeria, which are projected to account for one‐third of global urban population growth through 2050. Our results show that urban expansion slightly reduces heat stress during the day (∼0.2°C) but substantially intensifies it at night, by ∼1°C on average and by up to 2–3°C in five mega‐urban regions (MURs). These effects exist with or without climate change induced by rising concentrations of greenhouse gases (GHGs). Installing cool roofs—an urban heat island mitigation measures—can reduce the daytime WBGT by 0.5–1°C, partially offsetting the heat stress conditions caused by GHG‐induced climate change. However, even with cool roofs, the nighttime WBGTs are higher by 0.3–0.9°C over the whole countries studied, and by 1–2°C in the MURs under the urban expansion scenario, compared to the situation in which urban areas remain unchanged. These results show that future urban expansion and heat island mitigation can result in potential daytime benefits but also persistent nighttime risks. Key Points: Urban land expansion by 2050 will slightly reduce heat stress during the day but substantially intensifies it at night About half of the outdoor nighttime urban heat stress increases will persist even with cool roofs installed at large‐scale Possible complimentary adaptation measures include improving building insulation to reduce indoor heat stress